Effect of Valve Height on the Opening and Closing Performance of the Aortic Valve Under Aortic Root Dilatation - Hou, Qianwen; Liu, Guimei; Liu, Ning; Zhang, Honghui; Qu, Zhuoran; Zhang, Hanbing; Li, Hui; Pan, Youlian; Qiao, Aike (Frontiers in Physiology, 2021)
Patients with aortic valve disease can suffer from valve insufficiency after valve repair surgery due to the aortic root dilatation. The paper investigates the effect of valve height (HV) on the aortic valve opening and closing in order to make blood flow across the aortic valve more smoothly and valve closure completely in the case of continuous aortic root dilatation. A total of 20 parameterized 3-dimensional models of the aortic root were constructed following the clinical surgical guidance. The aortic annulus diameter (DAA) was separately set to 26, 27, 28, 29 and 30 mm to simulate the aortic root dilatation. The HV value was separately set to 13.5, 14, 14.5 and 15 mm to simulate the aortic valve alterations in surgery. Time-varying pressure loads were applied to the valve, vessel wall of the ascending aorta and left ventricle. Then, a finite element analysis software was employed to simulate the movement and mechanics of the aortic root. The feasible design range of the valve size was evaluated using the maximum stress, geometric orifice area (GOA) as well as leaflet contact force. The results show that the valve was incompletely closed when HV was 13.5 mm and DAA was 29 or 30 mm. The GOA of the valve was small when HV was 15 mm and DAA was 26 or 27 mm. The corresponding values of the other models were within the normal range. Compared with the model with an HV of 14 mm, the model with an HV of 14.5 mm could effectively reduce the maximum stress and had relatively larger GOA and less change in the contact force. As a result, the valve height affects the performance of the aortic valve opening and closing. Smaller HV is adapted to smaller DAA and vice versa. When HV is 14.5 mm, the valve is well adapted to the dilatation of the aortic root to enhance the repair durability. Therefore, more attention should be paid to HV in surgical planning.